Remimazolam for the prevention of emergence agitation in adults following nasal surgery under general anesthesia: a prospective randomized clinical controlled trial - Yanfei Lu; Qiaomin Xu; Hong Dai; Jimin Wu; Mengting Ai; Haiyan Lan; Xiaoli Dong; Gongchen Duan (BMC Anesthesiology)
Abstract Background Remimazolam is a novel intravenous sedative/anesthetic drug that belongs to the ultra-short-acting class of benzodiazepines. The purpose of this study was to evaluate the effectiveness of postoperative use of remimazolam in preventing emergence agitation (EA) in adults following nasal surgery. Methods Patients who underwent nasal surgery were randomly divided into Group R and Group C. Propofol, sufentanil, and cis-atracurium were used for the induction of anesthesia, and 1.5–3.5% sevoflurane was used for the maintenance of anesthesia. At the end of the surgery, patients were randomly assigned to receive either remimazolam 0.1 mg kg− 1 (Group R, n = 43) or 0.9% saline (Group C, n = 43). The primary outcome was the incidence of EA, which was defined as a Riker Sedation–Agitation Scale score > 4. The secondary outcomes included the incidence of severe EA, anesthesia, surgery characteristics, adverse events, mean arterial pressure, and heart rate (at different time points). Results A total of 86 adult patients completed the study. The incidence of EA was lower in Group R than in Group C (21% vs. 49%, P = 0.007). The incidence of severe EA was also lower in Group R than in Group C (2% vs. 19%, P = 0.035). The maximal Sedation–Agitation Scale score during emergence was lower in Group R 4 [range 4 to 4] than in Group C 5 [range 4 to 6] (P < 0.001). In addition, the incidence of hypertension and grade of cough in Group R were lower than in Group C (P = 0.024). During emergence, the mean arterial pressure and heart rate of group R showed more stability than those in group C. Conclusions Postoperative intravenous infusion of 0.1 mg/kg remimazolam into adult patients undergoing nasal surgery can reduce the incidence of EA and severe EA, and provide stable hemodynamics. Trial registration The trial was registered, before patient enrollment, in the Chinese Clinical Trial Registry ( www.chictr.org.cn ) (clinical trial number: ChiCTR2300075300; Principal Investigator: Gongchen Duan; date of registration: 31 August 2023; https://www.chictr.org.cn/bin/project/edit?pid=203928 ).